IMPLEMENTASI SISTEM INFORMASI SKRIPSI PADA STIKOM DINAMIKA BANGSA JAMBI - Desi (LPPM Universitas Dinamika Bangsa, 2020)
The process of undergraduate thesis activities of STIKOM Dinamika Bangsa is still carried out conventionally starting from the notification of thesis information in the wall magazine to manual registration and the data collection process still uses Microsoft excel whose files are stored in each part that processes the activity. In the process of the thesis activity there are several problems encountered, namely the limited time available resulting in the accumulation of data, data input errors, delays in the process of making the proposal seminar schedule, the determination of the thesis guide and the thesis trial schedule. In addition because there is no student thesis information system, there is also someone who is cheating by changing the title of the thesis unilaterally, and also fake signatures for the proposal revision sheet and guidance cards for submission of thesis hearings. The data submitted by students when registering is also often incomplete, this results in delays in making the schedule of existing activities. To overcome the existing problems, a thesis information system is needed that can be used by every actor involved in this activity according to their respective needs. The purpose of this research is to implement the thesis information system using the object oriented approach method with PHP programming language and the MySQL Database that is directly connected to the SISFO STIKOM Dinamika Bangsa. Keywords : Information System, Thesis, UML, Academik